Nanoscale Control of Homoepitaxial Growth on a Two‐Dimensional Zeolite. (9th December 2016) - Shete, Meera; Kumar, Manjesh; Kim, Donghun; Rangnekar, Neel; Xu, Dandan; Topuz, Berna; Agrawal, Kumar Varoon; Karapetrova, Evguenia; Stottrup, Benjamin; Al‐Thabaiti, Shaeel; Basahel, Sulaiman; Narasimharao, Katabathini; et al.
Abstract: Nanoscale crystal growth control is crucial for tailoring two‐dimensional (2D) zeolites (crystallites with thickness less than two unit cells) and thicker zeolite nanosheets for applications in separation membranes and as hierarchical catalysts. However, methods to control zeolite crystal growth with nanometer precision are still in their infancy. Herein, we report solution‐based growth conditions leading to anisotropic epitaxial growth of 2D zeolites with rates as low as few nanometers per day. Contributions from misoriented surface nucleation and rotational intergrowths are eliminated. Growth monitoring at the single‐unit‐cell level reveals novel nanoscale crystal‐growth phenomena associated with the lateral size and surface curvature of 2D zeolites.